The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10997-009-9093-x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance, family ownership and performance

Abstract: Corporate governance, Family ownership, Performance, Agency theory, Stewardship theory, Contingency theory, G34, G32, L25,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 25 publications
4
93
0
7
Order By: Relevance
“…They also provide a critical appraisal of the firm's direction, strategy and business approaches, and broaden the boards' perspectives [69]. Furthermore, a 2010 study in Italy found that family presence on the board of directors affects performance negatively, and that the presence of independent directors affects performance positively [70], and another 2010 study found an inverted U-shaped association between the number of family members on the board and performance [71]. A recent study in Taiwan found that family firms with high ownership concentration and low family board representation had a higher performance than those with the opposite characteristics, i.e., low levels of ownership concentration and high family board representation [72].…”
Section: Board Structurementioning
confidence: 99%
“…They also provide a critical appraisal of the firm's direction, strategy and business approaches, and broaden the boards' perspectives [69]. Furthermore, a 2010 study in Italy found that family presence on the board of directors affects performance negatively, and that the presence of independent directors affects performance positively [70], and another 2010 study found an inverted U-shaped association between the number of family members on the board and performance [71]. A recent study in Taiwan found that family firms with high ownership concentration and low family board representation had a higher performance than those with the opposite characteristics, i.e., low levels of ownership concentration and high family board representation [72].…”
Section: Board Structurementioning
confidence: 99%
“…The same combination of components can be found in very early and quite recent definitions: Generational transfer in interdependent subsystems (Dyer, 1964;Jaffe & Lane, 2004), voting control (Barry, 1975;Barnes & Hershon, 1976;Rue & Ibrahim, 1996), family management (Alcorn, 1982;Heck & Scannell 1999), family ownership (Tagiuri & Davis, 1982;Giovannini 2010) and ownership-management (Stern 1986;Donckels & Lambrecht 1999).…”
Section: Components and Essence Of Family Firmsmentioning
confidence: 75%
“…Different functions of BOC and BOD offer a lot of choices for the majority shareholder to involve owner family members in the BOC or BOD, and even in both boards. This apparent may increase the potential agency problem and information asymmetry between the two separate boards (Giovannini, 2010;Zhao & Millet-Reyes, 2007;Firth et al, 2007) and expect to provide a different impression on the performance of the firm. To see the impact of family involvement on firm performance as a whole including the physical assets and intellectual assets, this study uses VAIC method which is different from commonly used methods.…”
Section: Introductionmentioning
confidence: 99%